La prévention intégrée au travail : une conceptualisation basée sur les perspectives des parties prenantes canadiennes - Lily Bellehumeur-Béchamp; Andrée-Anne Drolet; Marie-Ève Major; Valérie Lederer; Claude Vincent; Alexandra Lecours (Perspectives Interdisciplinaires sur le Travail et la Santé)
Introduction. Integrative prevention in the workplace is a concept that is gaining popularity, but the limited amount of literature on the subject renders its definition incomplete. The perspective of individuals exposed to the concept could contribute to the development of an enhanced definition. Objective. The objective of this study is to refine the definition of integrative prevention at work established theoretically, by considering the perspectives of people exposed to the concept. Method. Using a descriptive-interpretive research design, individual interviews were conducted with 12 stakeholders involved in the continuum of work injury and disability prevention. A thematic analysis was performed on the data collected. Results. The results suggest that integrative prevention in the workplace is defined by five attributes: (1) a holistic vision of health, (2) a shared understanding of the purpose of integrative prevention, (3) communication between stakeholders, (4) collaboration between stakeholders, and (5) coordination of preventive actions. The analysis also highlighted the antecedents, or prerequisites for the implementation of the concept, as well as its consequences, or outcomes. Conclusion. This study provides an enhanced and nuanced conceptualization of integrated workplace prevention along with practical application guidelines.